An ‘environment to nucleus’ signaling system operates in B lymphocytes: redox status modulates BSAP/Pax-5 activation through Ref-1 nuclear translocation - Tell, Gianluca (Oxford University Press, 2000)
The Ref-1 (also called APE or HAP1) protein is a bifunctional enzyme impacting on a wide variety of important cellular functions. It acts as a major member of the DNA base excision repair pathway. Moreover, Ref-1 stimulates the DNA-binding activity of several transcription factors (TFs) through the reduction of highly reactive cysteine residues. Therefore, it represents a mechanism that regulates eukaryotic gene expression in a fast way. However, it has been demonstrated that external stimuli directly act on Ref-1 by increasing its expression levels, a time-consuming mechanism representing a paradox in terms of rapidity of TF regulation. In this paper we demonstrate that this is only an apparent paradox. Exposure of B lymphocytes to H(2)O(2) induced a rapid and sustained increase in Ref-1 protein levels in the nucleus as evaluated by both western blot analysis and by pulse–chase experiments. A time course, two color in situ immunocytochemistry indicated that the up-regulation of Ref-1 in the nucleus at <30 min was primarily the consequence of translocation of its cytoplasmic form. This early nuclear accumulation is effective in modulating the DNA-binding activity of the B cell-specific activator protein BSAP/Pax-5. In fact, EMSA experiments demonstrate that a transient interaction with Ref-1 up-regulates the DNA-binding activity of BSAP/Pax-5. Moreover, in a co-transfection experiment, Ref-1 increased the BSAP/Pax-5 activating effect on an oligomerized BSAP/Pax-5 binding site of the CD19 promoter by 5- to 8-fold. Thus, Ref-1 mediates its effect by up-regulating the DNA-binding activity of BSAP/Pax-5, accounting for a new and fast outside/inside pathway of signaling in B cells.